Inducible Clindamycin Resistance in Methicillin-Resistant and-Susceptible Staphylococcus aureus Isolated From South East of Iran - Mansouri, Shahla (Jundishapur J Microbiol, 2014)
BACKGROUND: Clindamycin is a frequently used antimicrobial therapeutic medicine used for the treatment of skin and soft tissue infections caused by Staphylococcus aureus strains. Resistance to this antibiotic is either constitutive or inducible. Constitutive resistance to clindamycin could be detected by standard susceptibility testing methods. Inducible clindamycin resistance could not be detected by in vitro routine tests. This type of resistance can be identified by D-test. OBJECTIVES: The outbreak of inducible resistance to clindamycin in methicillin resistant and-susceptible S. aureus isolates were investigated in this study. MATERIALS AND METHODS: Totally 162 S. aureus isolates were evaluated for inducible clindamycin resistance by D-test in accordance with clinical and laboratory standards institute (CLSI) guidelines. RESULTS: Inducible clindamycin resistance was detected in 8.64% of S. aureus isolates. Inducible and constitutive resistance to clindamycin was found to be higher in methicillin resistant S. aureus (11.95% and 47.8% respectively) compared to methicillin susceptible S. aureus (4.28% and 2.85% respectively) isolates. CONCLUSIONS: Our results showed that inducible resistance to clindamycin in S. aureus isolates is relatively higher in this region. Therefore, D-test should be performed to prevent treatment failures against infections caused by S. aureus, which are resistant to erythromycin and the sensitive ones against clindamycin.